Secure group mobility support for 6LoWPAN networks - Qiu, Yue (2020)
The Internet Protocol version 6 (IPv6) over low power wireless personal area networks (6LoWPANs) has introduced IP technologies to wireless sensor networks, which significantly promotes the development of the Internet of Things. To support effective mobility management of these resource constrained IP-based sensor nodes, the Proxy Mobile IPv6 has been proposed as a standard to minimize the communication over-head of those nodes. Although the standard has specified some issues of security and mobility in 6LoWPANs, the issues of supporting secure group handovers have not been addressed much by the currently existing solutions. To further reduce the handover latency and signaling overhead, a fast group authentication scheme is proposed in this paper to support secure and seamless handovers for multiple resource constrained 6LoWPAN devices. With the consideration of mobile sensors with limited energy, only simple hash functions and symmetric encryption algorithms are used. The security analysis and the performance evaluation show that the proposed 6LoWPAN group handover scheme could enhance the security functionalities with high efficiency to achieve a fast authentication for handovers.